Sweroside: unveiling broad therapeutic potential—from mechanistic insights to clinical potential - Peng, Liu; Zuo, Man; Qiu, Tian; Lan, Wenying; Wen, Yue; Ye, Xiao-Qin (Frontiers in Pharmacology, 2025)
BackgroundSweroside, a secoiridoid glycoside abundantly present in medicinal plants, has garnered significant attention due to its diverse bioactivities, including anti-inflammatory, antioxidant, hepatoprotective, antidiabetic, antibacterial, and anticancer effects. Additionally, it exhibits promising potential in neuroprotection and dermatological health.PurposeThis review aims to provide a comprehensive analysis of Sweroside, focusing on its sources, biosynthetic pathways, pharmacodynamic mechanisms, and therapeutic potential. The insights presented aim to facilitate the development of novel pharmacotherapies and advance precision medicine.MethodsA systematic review of the literature was conducted using databases such as PubMed, Web of Science, and Google Scholar. The study examined Sweroside’s sources, distribution, biosynthesis, pharmacodynamics, and therapeutic applications. Challenges in its clinical translation were also evaluated, with proposed strategies to enhance bioavailability.ResultsSweroside modulates critical signaling pathways, such as NF-κB, mTOR, MAPK, and PI3K/Akt, and their molecular substrates, contributing to its therapeutic effects across various pathological conditions. Preclinical studies demonstrate its efficacy in treating hepatic disorders, osteoporosis, cardiovascular diseases, and neurological dysfunctions. It also shows promise in neuroprotection and dermatological health. However, clinical translation is hindered by its low bioavailability and rapid metabolic degradation.ConclusionSweroside is a versatile natural metabolite with multi-target therapeutic potential, positioning it as a promising candidate for next-generation pharmacotherapies. To realize its clinical potential, future research should prioritize optimizing its pharmacokinetics, including enhancing bioavailability and developing advanced drug delivery systems. Further investigation into its molecular mechanisms and intracellular targets across diverse pathological conditions is essential. Sweroside’s integration into precision medicine offers significant opportunities for addressing chronic and complex diseases.